Prognostic factors and predictors of outcome in children with autism spectrum disorder: the role of the paediatrician - Magda Di Renzo; Federico Bianchi di Castelbianco; Villani Alberto; Del Vecchio Antonio; Corsello Giovanni; Elena Vanadia; Massimiliano Petrillo; Trapolino Davide; Lidia Racinaro; Monica Rea (BMC, 2021)
Abstract Background Autism spectrum disorder is a complex condition with wide variation in type and severity that involves persistent challenges in social interaction, speech and nonverbal communication, restricted/repetitive behaviours and adaptive behaviours. In recent years, research has deepened the study of the predictive factors of optimal outcome, intended as indicators of positive trajectory in children with a previous diagnosis of autism who, after a therapeutic path, show a significant reduction in the "core" symptoms of autism and a positive evolution in social, adaptive, affective, and relational skills. Methods The study included 40 children aged 21 to 66 months, enrolled between 2015 and 2016 for an autism spectrum disorder clinical suspicious. Children were re-evaluated after at least 2 years of therapy and they were divided into two groups: the ASD-ASD group included children with a confirmed diagnosis of ASD, and the ASD-OO comparison group included children who no longer met the criteria for an autism classification. The aim of this retrospective study was to investigate the presence of cognitive, emotional and relational predictors capable of predicting the presence of optimal outcome in with a diagnosis of autism; the predictors taken into consideration were the intelligence quotient, the play, the emotional contagion and the understanding of other's intentions. In this way, it is possible to support clinicians in defining a more complete diagnostic framework of autism, using assessment tools that can be administered quickly and therefore suitable for short observation sessions in paediatric patients. Results The findings showed that 15 out of 40 children, after at least for 2 years, no longer fell into the diagnostic ASD category based on the ADOS-2, DSM-5 and clinical criteria. The children in the ASD-OO group initially had a higher IQ than those in the ASD-ASD group, lower severity of autistic symptoms, greater understanding of intentions, more emotional contagion, and better quality of play. The results suggest that the initial coexistence of skills in these areas at the time of the first diagnostic assessment may allow us to predict the possibility of achieving optimal outcome after 2 years of therapy. Conclusions The data of this study highlight the importance of considering, during assessment, intelligence quotient, play, emotional contagion, and understanding of the intentions of others as potential prognostic predictors that can become useful tools for clinicians and paediatricians. This allows us to focus attention, in both the diagnostic and prognostic phases, on emotional-relational variables that can support the clinician in defining a more complete diagnostic framework and in planning a more personalized therapeutic path.